2016
DOI: 10.1111/psyp.12653
|View full text |Cite
|
Sign up to set email alerts
|

The accessory stimulus effect is mediated by phasic arousal: A pupillometry study

Abstract: People usually respond faster to a visual stimulus when it is immediately preceded by a task-irrelevant, auditory accessory stimulus (AS). This AS effect occurs even in choice reaction time tasks, despite the fact that the AS carries no information about the correct response. Researchers often assume that the AS effect is mediated by a phasic arousal burst evoked by the AS, but direct evidence for that assumption is lacking. We conducted a pupillometry study to directly test the phasic arousal hypothesis. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…We presented a target of fixed color and intensity, but manipulated the surrounding distractor stimuli to create different levels of competition in visual processing. Arousal level was successfully manipulated in three different ways, as evidenced by ERP modulations in response to emotionally arousing pictures (Experiment 1B), improvements in stimulus processing speed after the presentation of alerting auditory tones that are known to elicit a phasic arousal response (Experiment 2; Hackley & Valle-Inclán, 2003;Jepma et al, 2009;Tona et al, 2016), and by large increases in pupil diameter under white-noise stimulation (Experiment 3B). Two of these manipulations affected trial-to-trial changes in (phasic) arousal, one manipulation affected arousal in a blockwise (tonic) fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We presented a target of fixed color and intensity, but manipulated the surrounding distractor stimuli to create different levels of competition in visual processing. Arousal level was successfully manipulated in three different ways, as evidenced by ERP modulations in response to emotionally arousing pictures (Experiment 1B), improvements in stimulus processing speed after the presentation of alerting auditory tones that are known to elicit a phasic arousal response (Experiment 2; Hackley & Valle-Inclán, 2003;Jepma et al, 2009;Tona et al, 2016), and by large increases in pupil diameter under white-noise stimulation (Experiment 3B). Two of these manipulations affected trial-to-trial changes in (phasic) arousal, one manipulation affected arousal in a blockwise (tonic) fashion.…”
Section: Discussionmentioning
confidence: 99%
“…In Experiment 2 we used auditory alerting tones to induce arousal in participants, and compared task performance to a no-tone condition. A loud tone often induces a reflexive phasic arousal response (Hackley & Valle-Inclán, 2003;Tona, Murphy, Brown, & Nieuwenhuis, 2016), and can serve as a temporal cue for the participant to concentrate their efforts in a narrow interval of time.…”
Section: Introductionmentioning
confidence: 99%
“…The first type is the energy integration model, in which accessory stimuli facilitate stimulus encoding at early information processing stages (Bernstein, 1970;Stein, London, Wilkinson, & Price, 1996). This view is supported by evidence that the ASE is mediated by phasic arousal, which is indexed by pupil dilation during an early time window (Tona, Murphy, Brown, & Nieuwenhuis, 2016). An additive activation of multisensory neurons in the modality-specific areas serves as the neural mechanism of energy integration (Jepma, Wagenmakers, Band, & Nieuwenhuis, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, Niemi (1979) showed that foreperiod effects are reduced when the IS is an intense signal in the auditory modality, suggestive of a facilitatory effect of phasic arousal over the neural activity of circuits responsible for the initiation and execution of the voluntary response 81; Tona, Murphy, Brown, & Nieuwenhuis, 2016). This reduction of foreperiod effects when using an intense acoustic go-signal may reflect the activation of a specific physiological mechanism thought to be involved in the StartReact 5 effect (Valls-.…”
Section: Introductionmentioning
confidence: 99%